2017
DOI: 10.1007/s00705-017-3519-6
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of a novel calicivirus, FHMCV-2012, from baitfish in the USA

Abstract: During regulatory sampling of fathead minnows (Pimephales promelas), a novel calicivirus was isolated from homogenates of kidney and spleen inoculated into bluegill fry (BF-2) cells. Infected cell cultures exhibiting cytopathic effects were screened by PCR-based methods for selected fish viral pathogens. Illumina HiSeq next generation sequencing of the total RNA revealed a novel calicivirus genome that showed limited protein sequence similarity to known homologs in a BLASTp search. The complete genome of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Viruses of seven genera ( Lagovirus , Norovirus , Nebovirus , Recovirus [ 4 ], Sapovirus , Valovirus [ 5 ] and Vesivirus ) infect a wide range of mammals, members of two genera infect birds ( Bavovirus [ 6 ] and Nacovirus [ 7 ]) and members of two genera infect fish ( Minovirus [ 8 ] and Salovirus [ 9 ]), while caliciviruses have also been detected in the greater green snake and frogs [ 10 ], highlighting the wide host range of viruses in the family. Caliciviruses are similar to picornaviruses in the presence of VPg and in sequence similarity of their RNA-directed RNA polymerase and protease proteins.…”
Section: Taxonomymentioning
confidence: 99%
“…Viruses of seven genera ( Lagovirus , Norovirus , Nebovirus , Recovirus [ 4 ], Sapovirus , Valovirus [ 5 ] and Vesivirus ) infect a wide range of mammals, members of two genera infect birds ( Bavovirus [ 6 ] and Nacovirus [ 7 ]) and members of two genera infect fish ( Minovirus [ 8 ] and Salovirus [ 9 ]), while caliciviruses have also been detected in the greater green snake and frogs [ 10 ], highlighting the wide host range of viruses in the family. Caliciviruses are similar to picornaviruses in the presence of VPg and in sequence similarity of their RNA-directed RNA polymerase and protease proteins.…”
Section: Taxonomymentioning
confidence: 99%
“…ASCV is often detected as a coinfection with other agents (e.g., with PRV), but studies to date have had variable and often inconclusive findings for its independent pathological effects (Mikalsen et al 2014;Wiik-Nielsen et al 2016). Interestingly, a related fish calcicivirus in baitfish was associated with clinical disease only when coinfected with a second virus (Mor et al 2017). Given its widespread prevalence, future studies should evaluate sequence variation among ASCV isolates across geographic regions and examine the potential role ASCV plays in disease progression in coinfections.…”
Section: Infection Profiles Of Wild and Escaped Farm Salmon In Riversmentioning
confidence: 99%
“…However, ASCV was also commonly 150 found in healthy fish and a more recent study found no correlation between ASCV and HSMI (36,37). However, there is evidence that co-infection of caliciviruses with other viruses could be linked to clinical manifestations of disease in baitfish (38). In this study, in farmed Atlantic salmon from BC, we discovered viral genomes extremely closely related to the ASCV genome first discovered and sequenced in Norway (36).…”
mentioning
confidence: 57%
“…As expected, ASCV groups within a distinct clade from the mammalian caliciviruses ( Figure 3A), and is more 170 closely related to metatranscriptomic discovered fish caliciviruses (1) and fathead minnow calicivirus (38), a novel calicivirus isolated from farmed baitfish in Wisconsin, USA. It is becoming clear that caliciviruses are widespread in fish, and although we know very little of their direct role in lesion development, fish caliciviruses have been associated with diseased fish in an aquaculture setting (38). These newly described fish caliciviruses (1,38) are phylogenetically distinct from those first described in mammals, suggesting 175 that spillover from fish to mammals is not a common occurrence, as has been previously suggested (49, 50).…”
mentioning
confidence: 82%
See 1 more Smart Citation